SEROPREVALENCE AND RISK FACTORS OF BRUCELLOSIS IN CATTLE IN POLEWALI MANDAR DISTRICT, WEST SULAWESI - Aritayanthi, Ni Putu Novi; Mahatmi, Hapsari; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana, 2023)
The purpose of this study was to determine the seroprevalence of brucellosis in cattle in Polewali Mandar Regency, West Sulawesi; the distribution of the disease; and the risk factors associated with the incidence and distribution of brucellosis in Polewali Mandar Regency, West Sulawesi. The study was conducted by collecting cattle serum samples belonging to farmers in Polewali Mandar, West Sulawesi, then examined using the Rose Bengal Test (RBT) which was confirmed by the Complement Fixation Test (CFT). The risk factors for the incidence of brucellosis in cattle were studied by analyzing the relationship between the incidence of brucellosis in cattle and some data obtained from the results of questionnaires that distributed to cattle owners. Based on the results of the RBT and CFT tests, it was found that 15.17% (22/145) of serum was detected with brucellosis. This means that the prevalence of brucellosis in cattle in Polewali Mandar District, West Sulawesi was 15.17% based on point prevalence method. The incidence of brucellosis was distributed in 6 (six) sub-districts, namely Balanipa District with a prevalence of 18.75%; Campalagian 7.5%; Luyo 25.53%; Mapilli 50%, West Mapilli 100% and Polewali 25% in line with the ratio of positive samples from its total samples for every subdistrict sampled. The main risk factors associated with the incidence of brucellosis in Polewali Mandar Regency are abortion status which has an odds-ratio (OR) of 1220, livestock transportation has an OR of 17,333, and and the use of livestock drinking water has an OR of 9,343. Other risk factors are mating technology and cattle sex which have OR: 8022 and 4.053. The results of this research suggest that it is important to carry test and slaughter, also vaccination for prevention and eradication of brucellosis. It is imperative to place brucellosis control measures toward infected areas, such as, raising environmental health awareness, laboratory confirmed investigation on miscarriages, surveillance on livestock traffic, as well as periodical serology surveillance. Further research must be conducted to acquire a more thorough information on seroprevalence, spread, and risk factors of brucellosis all over West Sulawesi.